Performance evaluation on high speed machining of custom 465 steel - Prasath, V.; Krishnaraj, V.; Kanchana, J.; Priyadharshini, B. Geetha; Tewari, Ashish (Materials today : proceedings, 2017)
Custom 465 steel is a martensitic, age-hardenable alloy having a superior combination of strength and corrosion cracking resistance, which are commonly used in aerospace industries. When machining Custom 465 steel, tool-work interface temperature and tool wear are the major parameters which influences the machinability factors at a greater extend. Even though, researchers have performed many operations based on this subject, no significant data’s were available regarding the Custom 465 steel. A dry machining operation known for its ecological desirable and cost effective process was implemented to experimentally investigate the tool wear and tool-work interface temperature when machining Custom 465 steel using uncoated, TiAlN and TiCN coated carbide cutting tool inserts with a cutting speed of 100 m/min and 200 m/min and also the effects of cutting speed on tool wear and tool-work interface temperature were also determined. The highest tool life of 6.15 minutes was recorded for TiAlN coated insert at a cutting speed of 2000 rotations per minute (rpm), feed rate of 200 mm/min and depth of cut of 0.5 mm. The maximum tool wear recorded for TiAlN coated insert was 0.25 mm and the maximum temperature on the tool-work impact was 142.43 degrees. In all cutting speeds, TiAlN coated insert outperformed uncoated and TiCN coated insert in term of tool life and temperature. For a cutting speed of 2000 rpm and above uncoated inserts are not suitable to be used for machining Custom 465 steel due to the rapid wear of cutting edge.